PENGARUH PENERAPAN MODEL COOPERATIVE SCRIPT DISERTAI HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 BASA AMPEK BALAI TAPAN KABUPATEN PESISIR SELATAN - Yohanda, Early; Anggraini, Villia; Yuliana Fitri, Dewi (STKIP PGRI Sumbar, 2013)
Background of this research was students understanding of mathematical concept and students rarely make a summary of the materai provide by the teacher. Study was to examine students understanding of mathematical concept using a model of cooperative script with handout is better than the students understanding of mathematical concepts using conventional learning